Non-innocent redox behavior of CuII–p-dimethylaminophenolate complexes: formation and characterization of the CuI–phenoxyl radical species. Issue 44 (11th May 2022) - Shima, Yuto; Suzuki, Takashi; Abe, Hitoshi; Yajima, Tatsuo; Mori, Seiji; Shimazaki, Yuichi
Abstract : The reaction of Cu II ion with dimethylaminophenolate ligands gave Cu I –phenoxyl radical complexes under inert gas atmosphere in the absence of solvent coordination, and their electronic and geometric structures and reactivities were characterized. Abstract : Cu complexes with p -dimethylaminophenolate ligands were synthesized by the reaction of Cu II ions with the ligands under inert gas atmosphere and characterized. The complexes showed a valence state change from Cu II –phenolate to Cu I –phenoxyl radical on loss of the coordinated solvent. The Cu I –phenoxyl radical species showed the characteristic properties and reactivities.